Beliefs About Love Marriage: Development and Validation of a Psychological Questionnaire - Saba Kanwal; Jawaria Ashraf; Ather Mujitaba; Tehreen Shehbaz; Mahnoor Afzal (Research Journal of Psychology, 2025)
In the Pakistani cultural context, love marriage often perceived as a challenge to traditional norms, family expectations, and societal cohesion. Despite the increasing visibility of love marriages related beliefs and attitude discrepancy among young educated populations there has been a lack of culturally sensitive psychological tools to systematically assess beliefs regarding love marriage. Recognizing this gap, the present study aimed to develop and validate the Positive and Negative Beliefs about Love Marriage Questionnaire (PNBLM-Q) an indigenous, psychometrically sound measure that captures the nuanced perspectives individuals hold toward love marriage in Pakistan. The scale was developed through a rigorous multi-phase process including qualitative interviews, thematic analysis, expert review, and empirical validation. A total of 312 participants (aged 18–35) took part in the study. Exploratory factor analysis supported a two-factor model reflecting positive and negative belief dimensions, accounting for 58.8% of the total variance. Both subscales demonstrated high internal consistency (α = .92 for positive beliefs, α = .89 for negative beliefs). The two subscales were significantly negatively correlated (r = –.23, p < .01), suggesting that individuals who hold stronger positive beliefs tend to endorse fewer negative beliefs. Gender analysis revealed that females reported significantly higher positive beliefs than males, while no significant difference was observed in negative beliefs. The PNBLM-Q offers a culturally grounded and empirically validated tool for researchers, clinicians, and counselors seeking to understand how evolving social norms, emotional expectations, and traditional values shape attitudes toward love marriage in contemporary Pakistani society.